Effectiveness of some aflatoxin interventions in reducing the aflatoxin contamination of maize in Ghana - Kaburi, Sandra Ama; Lamptey, Francis Padi; Otoo, Gifty Serwaa; Appiah, Francis (Journal of Food Technology Research, 2023)
The presence of aflatoxin in food and feed represents a significant health hazard to both human and animal populations, hence exerting adverse effects on the environment and the global economy. The effects of maize variety, agroecological zones, and aflatoxin control measures on aflatoxin contamination were tested using a 2x2x3 factorial in a randomised complete block design (RCBD). The treatments consisted of two agroecological zones, two varieties of maize, and three aflatoxin control measures. The aflasafe was applied at a rate of 10 kg/ha and the nicoking at 200 ml per 15 liters of water. There was no contamination of maize samples grown in the Forest zone with aflatoxins during all the treatments. There was no contamination of maize samples with aflatoxins BI, B2, G1, and G2 for all the treatments in the Savannah zone except for the hoeing method. The highest contamination of Aflatoxin G2 (AFG2) (0.19 µg/kg) was recorded by the Wangdataa maize variety using hoeing as the means of the aflatoxin control method. The highest Aflatoxin G1 (AFG1) contamination (0.45 µg/kg) was produced by maize grown in the Savannah ecozone using the hoeing method of control. In conclusion, the study showed that all the control methods gave maximum protection to the maize while growing on the field except the hoeing method in the Savannah ecological zone. The study recommends that in the Savannah zone if a farmer chooses hoeing as a method to control aflatoxins, it is advisable to complement this approach with the use of biological or chemical methods for effective aflatoxin control.